2009
DOI: 10.1063/1.3234248
|View full text |Cite
|
Sign up to set email alerts
|

Fast ignition of inertial fusion targets by laser-driven carbon beams

Abstract: Two-dimensional simulations of ion beam driven fast ignition are presented. Ignition energies of protons with Maxwellian spectrum and carbon ions with quasimonoenergetic and Maxwellian energy distributions are evaluated. The effect of the coronal plasma surrounding the compressed deuterium-tritium is studied for three different fuel density distributions. It is found that quasi- monoenergetic ions have better coupling with the compressed deuterium-tritium and substantially lower ignition energies. Comparison o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 37 publications
1
69
0
Order By: Relevance
“…It presents, however, a large coronal plasma surrounding the core which clearly overestimates the plasma densities from the cone apex to the DT core when compared with the density profiles obtained in cone-target simulations [29]. As ignition energies depend substantially on the areal density of the coronal plasma [23], the 1D imploded target density distribution shown in Fig. 1a allow us to obtain an upper limit of the ignition energies for the beam conditions studied.…”
Section: Simulation Modelmentioning
confidence: 75%
See 1 more Smart Citation
“…It presents, however, a large coronal plasma surrounding the core which clearly overestimates the plasma densities from the cone apex to the DT core when compared with the density profiles obtained in cone-target simulations [29]. As ignition energies depend substantially on the areal density of the coronal plasma [23], the 1D imploded target density distribution shown in Fig. 1a allow us to obtain an upper limit of the ignition energies for the beam conditions studied.…”
Section: Simulation Modelmentioning
confidence: 75%
“…This was followed by theoretical studies on the TNSA scheme [16,17], target studies [18][19][20][21], new irradiation schemes [9,11,12] and the use of ions heavier than protons [22,23]. Other schemes such as the two-pulse scheme described in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In previous works, we showed that quasimonoenergetic ions have a higher coupling efficiency and lower ignition energies than the standard FI scheme with Maxwellian ions [9]. Here, in order to explore 03013-p. 4 IFSA 2011 the full potential of IFI, we have investigated the use of lithium, carbon, aluminium and vanadium quasimonoenergeticions to ignite a simplified DT fuel configuration with a peak density of 500 g/cm 3 .…”
Section: Discussionmentioning
confidence: 94%
“…Defining the optimal ion energy 0 as that for which the minimum E ig is obtained, the shape of these curves can be explained as follows. For kinetic energies lower than 0 , the pulse has a relatively low power, P ∝ 1/2 , and long duration, ∝ −1/2 [9], separating from the optimal shape and increasing E ig . For higher kinetic energies, E ig increases again due to the higher fuel mass heated by the ion beam.…”
Section: Ignition Energies For the Single Beam Schemementioning
confidence: 99%
See 1 more Smart Citation